Hedersmordet på Fadime: Debatt, fenomen, projektion - Ekström, Simon (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
The debate on the "honour killing of Fadime" can be described as one of a fundamental opposition. On the one hand there are those who argue that the murder can only be understood and be meaningful with reference to concepts such as culture and difference. On the other hand, there are those who, for different reasons, oppose such a culturally oriented understanding in favour of some other explanation. In this article, I argue that the murder, the legal handling, the mass media reporting and the subsequent debate became something that was used and exploited in an arena that is ultimately about competing descriptions of reality. The legal, media and the academic repercussions following the murder of Fadime Sahindal took the form of a discussion — which is still ongoing — about what the reality of the situation was, which definition of the problem was closest to the truth and what the best solutions were.